Paediatric Circumcision with Bipolar Diathermy: Our Experience of 200 Cases, Assessment of Health Benefits and Risks : Paediatric Circumcision with Bipolar Diathermy - Haider, Naveed Haider; Shahbaz, Ferheen; Varda, Komal; Saleem, Javeria; khizir, Ubaid Ur Rehman; Yasir Sultan, Muhammad (Pakistan Journal of Health Sciences, 2022)
Ritual circumcision is the most commonly used procedure for males. Circumcision operations are routine procedures, which are done using various techniques. Objective: To elaborate on the advanced techniques for bipolar diathermy by describing this surgical procedure in terms of incidence of postoperative complications, bleeding, and occurrence of infections or complications. All these findings were recorded in quantitative terms and a comparative analysis was made. Methods: A descriptive observational study was conducted on children of age 1 week to 8 years. The method was to observe readings for children undergoing circumcision procedures of bipolar diathermy. The p-value was calculated for postoperative complications. Results: We selected the target population of 200 children. There was a very reduced incidence of bleeding was recorded in children undergoing circumcision by bipolar diathermy. There were no infection rates recorded and very less post-operative complications. Conclusions: Bipolar diathermy method is more efficient with a decrease incidence of morbidities.